(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Soft tissue defect on the dorsal surface of the finger is a common injury. The cause is usually trauma, burns or infection. Covering the tendons and bones of this area, the dorsal metacarpal artery perforator branch flap (DMAPF) is one of the possible options. Case presentation: A 48-year-old male patient was admitted to the hospital because of a skin loss on the dorsum of the proximal phalanx index finger. The defect with tendon exposed is about 2x3cm in size. The patient underwent treatment with a DMAPF to cover the extensor tendon. 7 days after surgery, the skin flap had epidermolysis at the distal end of the flap. The skin flap survives completely after 15 days. After 3 years of follow-up, the patient recovered almost completely with DASH-score 0.8/100, and the patient was very satisfied with aesthetic factors. Discussion: DMAPF has been reported a lot around the world, but not much research has been seen in our country. This case shows the clinical applicability of DMAPF: one-stage flap, good functional and aesthetic recovery. Conclusion: The DMAPF has a relatively constant vascular pedicle that has been reported by many studies around the world. The thickness and color of the flap are very suitable for covering the defect on the dorsal finger, donor site morbidity is insignificant.